The Influence of Fernald Method to Increase Early Writing Skill of Students with Intellectual Disability in Grade II of SLB Panca Bakti Mulia Surakarta 2018-2019 - Widiamoksa, Garit (Indonesian Journal of Disability Studies, 2019)
This research aims to determine the influence of Fernald method to increase early writing skill of students with intellectual developmental disorder in grade II of SLB Panca Bakti Mulia Surakarta in academic year 2018/2019. This research used pre-experimental design with one group pretest-posttest design. The sample of this research is five students with intellectual developmental disorder in II grade of SLB Panca Bakti Mulia Surakarta in academic year 2018/2019, using saturation sampling technique. The research instrument uses a written test in the form of a short answer, namely a written test that thickens words, copies words, and completes words. The results of this study were analyzed using a signed ranking test (Wilcoxon Sign Rank Test). Based on the data analysis that has been done, it is known that the value of Zcount = -2,060 with Asymp. Sig. (2-tailed) of 0.039 which is below the significance level (p <0.05). These results indicate that the Fernald method has an effect on improving the writing skills of beginning class II students with intellectual developmental disorder at SLB Panca Bakti Mulia Surakarta Academic Year 2018/2019.